Analisis Buku Ajar Bahasa Arab Kelas XII Madrasah Aliyah Berdasarkan KMA 183 Tahun 2019 - Nazilah, Azza; Afia, Difla; A, Salsabila Humairo (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2023)
This study aims to find out the contents of the material, review, and analyze Arabic textbooks for class XII MA published by the Directorate General of Islamic Education, Ministry of Religion of the Republic of Indonesia on KMA No 183 of 2019 which consists of four Core Competencies (KI) as its perspective. The approach taken is a descriptive-qualitative approach using documentation and content analysis as tools for collecting and analyzing data. This form of analysis consists of four aspects, namely content, presentation, language, and graphics. The results of this study show that the content of the material is in accordance with the KMA Content Standards (KI) No. 183 of 2019, as detailed below: 1) the first chapter is more prominent in aspects of the realm of Knowledge (KI 3) Skills (KI 4) 2) the second chapter is the domain Knowledge (KI 3), Social (KI 2) and Skills (KI 4) 3) third chapter Spiritual domain (KI 1), Knowledge (KI 3) Skills (KI 4) 4) fourth chapter Spiritual domain (KI 1) and Skills (KI 4) 5) the fifth chapter is the domain of Knowledge (KI 3), Social (KI 2) and Skills (KI 4). There are all skill domains because each chapter covers the skills contained in Arabic, namely Reading (qiro'ah), Writing (kitabah), Listening (istima'), and Speaking (kalam) Skills.Keywords: Arabic Textbooks, Arabic Speaking Skills, Arabic Reading Skills, Arabic Listening Skills, Arabic Writing Skills